2022
DOI: 10.3390/medicina58111602
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Disrupts Glycemic Control in Obese Individuals

Abstract: The link between obstructive sleep apnea (OSA) and obesity, and their common comorbidities such as diabetes mellitus (DM) or cardiovascular diseases, is not fully understood. The aim of this study was to investigate the possible association of OSA severity in obese individuals with polysomnography-based sleep parameters, as well as C-reactive protein (CRP) and glycated hemoglobin (HbA1c) serum levels. Polysomnographic recordings and blood samples were retrospectively compared between a group of 23 adult obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…OSA appears to be an independent risk factor for developing T2D, insulin resistance and glucose intolerance ( Figure 2 ) [ 139 , 140 ]. Thus, in patients with T2D, OSA and higher oxygen desaturation levels were associated with higher glycated haemoglobin (HbA1c) levels [ 141 , 142 , 143 , 144 ].…”
Section: Osa and Metabolic Dysfunctionmentioning
confidence: 99%
“…OSA appears to be an independent risk factor for developing T2D, insulin resistance and glucose intolerance ( Figure 2 ) [ 139 , 140 ]. Thus, in patients with T2D, OSA and higher oxygen desaturation levels were associated with higher glycated haemoglobin (HbA1c) levels [ 141 , 142 , 143 , 144 ].…”
Section: Osa and Metabolic Dysfunctionmentioning
confidence: 99%
“…Furthermore, OSA prevalence increases with growing age and is more frequently seen in males [ 4 , 5 ]. Previous studies have shown that OSA is related to risk of glaucoma [ 6 ], non-alcoholic hepatic steatosis [ 7 ], unfavorable oncologic outcomes following therapy for head and neck squamous cell carcinoma [ 8 ], coronary artery disease [ 9 ], stroke [ 10 ], arterial hypertension [ 11 ], and other adverse effects [ 12 ]; therefore, OSA is recognized as an important public health issue.…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent hypoxemia results from increased sympathetic activity and is additionally associated with reductions in cerebral blood flow, dysregulated cerebral autoregulation, impaired endothelial function, increased intracerebral pressure, and platelet activation, inflammation, and oxidative stress, all of which exacerbate forms of neurological and cardiovascular injuries [ 2 ]. With these contributing factors, OSA has been convincingly linked to the intensification of several comorbid conditions, including cardiovascular disease [ 3 , 4 , 5 ], earlier mortality [ 6 , 7 ], cancer [ 8 ], insulin resistance [ 9 ], obesity [ 10 ], and greater stroke incidence [ 11 , 12 ]. Approximately 80% of OSA cases are considered ‘moderate to severe,’ and the disorder is highly underdiagnosed.…”
Section: Introductionmentioning
confidence: 99%